AN EMPIRICAL STUDY ON PARENTS' CHOICES APPLY ON ALTERNATIVE EDUCATION: A CASE STUDY OF T SCHOOL IN BEIJING - Yen-Ting, Lin (PEOPLE: International Journal of Social Sciences, 2020)
Since the end of the 20th century, education reform has been carried out all over the world. In one hand, the system of public school education cannot be recognized and satisfied by parents, and alternative education is one of the replacements. Through ethnographic research, the author participated in school activities, interview parents and micro-school APP interaction simultaneously, and use snowball sampling method to expand the depth and breadth of interviews. The purpose of this paper is to find out the differences between the school-running visions declared by schools verses the educational choices applied to parents. Try to classify what kind of parents will choose alternative education, and to reflect on the public education reform through their practices.